ANALISIS EFISIENSI DAN DAYA SAING KOMODITAS PADA SISTEM USAHATANI INTEGRASI JAGUNG-SAPI DI KABUPATEN KUPANG - , Ir. Siviardus Marjaya MMA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Integration Efficiency of corn-cattle integration farming system in Kupang district will determine the products that can compete in the market, as well as employment opportunities and provide income for farmers. This study aims to analyze the factors that affect production, income, efficiency and competitiveness of the corn-cattle integration farming system in Kupang district. The data used is the production data during the growing season of maize and cattle rearing period. The analysis model used is the analysis of the production function Cobb-Douglas Stochastic Frontier model of Battese and Coelli, 1995 with an option for Technical Efficiency Effects Model. The results of stochastic frontier production function estimation on the integration of maize-cow farm in Kupang regency were technically efficient, because the value of the average technical efficiency of maize farming is 0.957, and the cattle business is 0.999. Factors of age, education, experience and number of dependents does not significantly affect the technical efficiency of farming. Estimation results indicate that the value of the cost function cost efficiency (cost efficiency) corn-cattle integration farm is greater than one (CE > 1) that is 1,009 and 1,268. It means that the use of the cost of production factors on maize-cow integration farm should be reduced in order to achieve optimal efficiency. PAM results showed that the private benefit derived from corn-cattle integration farming system is Rp 21,029,163 per farming unit, the social benefits of Rp 12,172,583, while the value of divergence is Rp 8,856,581. It means that the corn-cattle integration farming system in Kupang district must spend more on domestic factors than tradable input costs. One reason is the policy regarding the minimum wage. Private cost ratio (PCR) of corn-beef integration farming is 0.535 smaller than one, meaning that the integration of the corn-cattle farm financially efficient or have a competitive advantage and can spur the production growth. While the value of domestic resources ratio (DCR) is 0.333, it means that the corn-cattle integration farming is economically efficient or have a comparative advantage.